Immigrant artists' intercultural identity formation and development process through art making - Jelekäinen, Emmi (2015)
The present study examines how immigrant artists view their intercultural identity formation and development process through art making. The study is based on a theoretical foundation combining the concepts of identity, immigration and art. Art is commonly seen closely connected to one’s self and experiences, and therefore it is possible that great changes in life, such as immigration, have an influence on one’s art and vice versa. Because immigration is becoming more and more common, it is important to take into account also the emotional aspect of immigration through listening the thoughts and experiences of the people who are immigrants themselves to get more information about the ways people make sense of living in a foreign culture. In the theoretical part of the study first the concepts of immigration and cultural identity are discussed, from which the focus proceeds to the connections between immigration, art and cultural identities.